Financial Inclusion in India –A progress and Challenges - et al., Dr.G.Vincent (International Journal of Advanced Science and Technology, 2019)
Overcoming poverty is not a gesture of Charity. It is an act of justice. It is a protection of a fundamental rights, the right to dignity and a decent life. While poverty persists, there is no true freedom. Sometimes it falls upon a generation to be great. You can be that great generation. Let your greatness blossom. Of course the task will not be easy. But not to do this would be a crime against humanity, against which I ask all humanity now to rise up”